Nano-graphitic sponges and methods for fabricating the same

The method of distributing graphite in a molten polymer phase and applying shear strain events to exfoliate graphene nanoparticles addresses dispersion and agglomeration issues, resulting in nanographite sponges with enhanced conductivity and mechanical properties for diverse applications.

JP2025004177APending Publication Date: 2025-01-14RUTGERS THE STATE UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024177008
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-10-15
Filing Date
2024-10-09
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing methods for manufacturing nanographite sponges face challenges such as poor dispersion of graphene in polymer matrices, restacking and agglomeration of graphene sheets, and high loading of fillers that hinder processability and overall properties, limiting the electrical and thermal conductivity of composites.

Method used

A method involving the distribution of graphite microparticles into a molten thermoplastic polymer phase, followed by a series of shear strain events to exfoliate graphene nanoparticles, and subsequent heating to decompose the polymer and form nanographite sponges with a three-dimensional interconnected network, which can be further modified with electroactive elements.

Benefits of technology

The method produces nanographite sponges with improved electrical and thermal conductivity, enhanced mechanical properties, and a customizable open cell structure suitable for various applications, including batteries, supercapacitors, and catalysts, while maintaining processability and structural integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025004177000001
    Figure 2025004177000001
  • Figure 2025004177000002
    Figure 2025004177000002
  • Figure 2025004177000003
    Figure 2025004177000003
Patent Text Reader

Abstract

To provide methods for preparing the nano-graphitic sponge.SOLUTION: A method for forming a nano-graphitic sponge comprises: (a) distributing graphite microparticles into a molten thermoplastic polymer phase; (b) applying a succession of shear strain events to the molten polymer phase, thereby forming a graphene-reinforced polymer matrix composite; (c) heating at the melting temperature of the polymer phase or at a temperature near and higher than the melting temperature; (d) heating the graphene-reinforced polymer matrix composite at the gasification temperature of the polymer or at a temperature near and higher than the gasification temperature for a duration of time sufficient to degrade and gasify the polymer to form a nano-graphitic sponge; (e) heating the nano-graphitic sponge until the residual polymer decomposes such that graphite / graphene particles accounts for 70 to 100 wt% of the total weight of the nano-graphitic sponge.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority under 35 U.S.C. §119(e) to U.S. Provisional Patent Application No. 62 / 745,839, filed October 15, 2018, which is incorporated by reference herein in its entirety.

[0002] The present disclosure relates to nano-graphite sponge (NGS) and a method for producing the nano-graphite sponge from a graphene-reinforced polymer matrix (G-PMC). [Background technology]

[0003] Graphene, a two-dimensional (2D) monolayer of carbon atoms, has attracted much attention due to its fascinating properties such as high electrical conductivity, high thermal conductivity, extraordinary elasticity, and stiffness. Graphene-based polymer composites with high electrical and thermal conductivity are highly desirable for many practical applications such as electronic devices, electromagnetic shielding, and thermal management.

[0004] However, the application of graphene-based polymer composites is limited by: (1) poor dispersion of graphene in the polymer matrix due to the large specific surface area and strong intermolecular interactions between graphene sheets; and (2) at low filler content, the graphene sheets are covered by polymer chains, preventing the graphene sheets from reaching the percolation limit of the composite. Since the electrical and thermal conductivity of these composites strongly depends on the percolation of electrons and phonons between isolated filler particles, to improve the electrical conductivity of the composites, good dispersion of graphene sheets and high filler content are required to form a conductive interconnected network within the polymer matrix.

[0005] To achieve better dispersion of graphene in the polymer matrix, strategies such as molecular functionalization have been investigated. However, while improving dispersion, molecular functionalization also damages the electronic conjugation of the graphene sheets, impairing the electrical conductivity of the composites. Despite the improved homogeneous distribution, the electrical conductivity of these composites is still far below expected levels. Furthermore, high loadings of fillers generally hinder the processability and overall properties of the composites due to severe agglomeration and poor interfacial bonding.

[0006] The construction of 3D compactly interconnected graphene networks (e.g., nanographite sponges (NGS)) can provide a significant increase in the electrical and thermal conductivity of polymer composites. Several methods have been proposed to fabricate NGS, including self-assembly strategies such as one-step hydrothermal methods, chemical reduction-induced methods, and metal ion-induced processes. However, restacking and aggregation of graphene sheets during assembly remains a serious problem. Therefore, it remains a challenge to fabricate NGS with the desired graphene 3D networks.

[0007] Therefore, there is a pressing need for a facile, low-cost, and scalable method for producing nano-graphite sponges (NGS). Summary of the Invention

[0008] The present disclosure provides a novel nano-graphite sponge (NGS) and a method for making the NGS. The NGS may include particles selected from the group consisting of graphite microparticles, single-layer graphene nanoparticles, multi-layer graphene nanoparticles, and combinations of two or more thereof. The particles may include mechanically exfoliated single-layer and / or multi-layer graphene nanoparticles. In some embodiments, the single-layer and / or multi-layer graphene nanoparticles are less than 50 nm thick along the c-axis direction. In some embodiments, the particles may comprise at least 50% of the total weight of the sponge. In some embodiments, the NGS further includes carbon particles. In some embodiments, the NGS further includes a thermoplastic polymer.

[0009] The NGS disclosed herein may have an open-cell structure including a plurality of open cells. The open cells may have various shapes, sizes, and dimensions. In some embodiments, the average pore size of the open cells ranges from about 1 nm to about 5 mm. The open cells may include additional elements encapsulated within the open cells. Examples of the additional elements may include Li, S, Si, Na, and combinations of two or more thereof. The NGS may include other salts (e.g., metal salts), such as Li salts (e.g., LiCoO2, LiMn2O4, LiFePO4, LiOH, Li2CO3, LiCl, Li2SO4, HCOOLi, CH3COOLi, Li3(C6H5O7), (COOLi)2, Li2S, Li2S2), and the like.

[0010] The NGS may be manufactured in any shape or form, in various sizes / dimensions. In one example, the NGS may be formed into a block. In another example, the NGS may be formed into a thread. The thread may have a diameter ranging from about 1 μm to about 10 mm. The thread may be further manufactured into pellets with lengths ranging from about 1 μm to about 10 mm. The thread may also be further manufactured into a powder form having a size ranging from about 0.1 μm to about 100 μm. The thread may be impregnated with a metal, whereby the metal is impregnated into the open cells and coated on the surface of the thread. In some embodiments, the thread may further include an insulating coating thereon to form a lightweight insulated conductive wire.

[0011] Further, the NGS may be formed into a sheet / film. The sheet / film may have a thickness ranging from about 1 μm to about 10 mm. The sheet / film may be wound into a hollow-core spiral tube. The hollow-core spiral tube may have a diameter ranging from about 10 μm to about 10 mm. In some embodiments, the spiral tube includes one or more layers of the sheet / film. The spiral tube may further include one or more layers of the sheet / film wound around a metal wire in the center of the spiral tube. In some embodiments, the spiral tube may include an insulating coating thereon to form a lightweight insulated conductive wire.

[0012] The present disclosure also provides an electrode comprising a sponge structure made from NGS blocks, NGS yarns, or NGS sheets / films. The electrode may be an anode or a cathode and may further comprise an insulating film for separating the sponge structure from adjacent sponge structures. Also contemplated in the present disclosure is a rechargeable battery comprising the described electrode and a transport liquid medium. The secondary battery may further comprise an insulating film for insulating the anode and the cathode, where the electrode is in the form of a film and is folded one or more times with the insulating film. The electrode and insulating film may be rolled into a cylindrical or flat pouch shape.

[0013] The NGS may include thermoplastic polymer chains intermolecularly crosslinked to the single- and multi-layer graphene nanoparticles via covalent bonds. In some embodiments, the single- and multi-layer graphene nanoparticles are doped with other elements to modify the surface chemistry. For example, the surface chemistry or nanostructure of the exfoliated single- and multi-layer graphene nanoparticles may be modified to increase the bond strength with the polymer matrix and increase the strength and stiffness of the polymer matrix composite and NGS.

[0014] The NGS may comprise a thermoplastic polymer molecule covalently bonded to one or more of the single-layer and / or multi-layer graphene nanoparticles, respectively, hi some embodiments, the NGS may comprise at least one thermoplastic polymer molecule bonded or adhered to one or more mechanically exfoliated single-layer or multi-layer graphene nanoparticles.

[0015] The thermoplastic polymer may be acrylic, polymethyl methacrylate (PMMA), acrylonitrile, acrylonitrile butadiene styrene (ABS) copolymer, polyacrylonitrile (PAN), aromatic polysulfone, aromatic thermoplastic polyester, liquid crystal polymer, polyaryletherketone, polycarbonate (PC), polyetheretherketone (PEEK), polyetherimide (PEI), polyetherketone (PEK), polyethylene, sulfurized polyethylene (PES), polyethylene terephthalate (PET or PETE), low density polyethylene (LDPE), high density polyethylene (HDPE), polyglycolic acid (PGA), polylactic acid (PLA), polylactic-glycolic acid copolymer (PLGA), polyoxymethylene plastic (POM / acetal), polyphenylene ether, polyphenylene oxide (PPO), polyphenylene sulfide (PPS), polypropylene (PP), polystyrene (PS), polysulfone (PSU), polytetrafluoroethylene (PTFE / TEFLONO), polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), thermoplastic elastomers, thermoplastic polyethylene, ultra-high molecular weight polyethylene (UHMWPE), polyamide (PA), aliphatic polyamides, semi-aromatic polyamides, aromatic polyamides, polyamide-11 (nylon-11), polyamide-12 (nylon-12), polyamide-4,6, polyamide-6 (nylon-6), polyamide-6,10, polyamide-6,12, polyamide-6,6 (nylon-6,6), polyamide-6,9, polyamide (PA), and mixtures of two or more thereof.

[0016] The present disclosure also provides an article of manufacture comprising the above-mentioned NGS, which may be a battery component, a supercapacitor component, a sensor component, a fuel cell component, a solar cell component, a catalyst, a catalyst support material, or an absorbent. For example, the article may be an electrode (e.g., an anode, a cathode) of a battery or a capacitor. The article may be a rechargeable battery having a first electrode comprising an NGS capable of intercalating an alkali metal, a counter electrode capable of intercalating an alkali metal, and an electrolyte comprising an organic solvent and a salt of an alkali metal in contact with the first electrode and the counter electrode.

[0017] The present disclosure also provides a method for forming an NGS, the method comprising: (a) distributing graphite microparticles into a molten thermoplastic polymer phase; (b) applying a series of shear strain events to the molten polymer phase, the molten polymer phase successively exfoliating graphite with each event until at least 1 wt%, optionally at least 5 wt%, optionally at least 10 wt%, optionally at least 20 wt%, optionally at least 50 wt%, optionally at least 75 wt%, optionally at least 95 wt% of the graphite is exfoliated to form a distribution in the molten polymer phase of single and multi-layer graphene nanoparticles smaller than 50 nm along the c-axis direction, thereby forming a graphene-reinforced polymer matrix composite; and (c) heating the graphene-reinforced polymer matrix composite until the polymer decomposes and gasifies to form an NGS. In some embodiments, the method further comprises: (d) vapor or liquid infiltrating the NGS with a precursor containing an electroactive element to form an NGS intercalated with the electroactive element.

[0018] In some embodiments, the method further comprises forming a uniform distribution of one or more additives in the molten polymer phase, the additives facilitating the intercalation of electroactive elements into the NGS. In some embodiments, the graphite particles are incorporated into the polymer matrix using a single screw extruder equipped with axially grooved elongational mixing elements or helically grooved elongational mixing elements. In some embodiments, the graphite-containing polymer matrix is ​​repeatedly extruded to induce exfoliation of the graphite and form a uniform dispersion of graphene nanoparticles in the polymer matrix.

[0019] In some embodiments, distributing the graphite comprises distributing the graphite, including graphite microparticles, into a molten thermoplastic polymer phase, where at least 10 wt%, sometimes at least 20 wt%, sometimes at least 30 wt%, sometimes at least 40 wt%, and sometimes at least 50 wt% of the graphite consists of multi-layer graphite crystals having a thickness along a c-axis direction of 1.0 to 1000 microns. In some embodiments, applying the series of shear strain events comprises applying a series of shear strain events to the liquid thermoset polymer precursor phase such that the shear stress in the polymer precursor phase is equal to or greater than the interlaminar shear strength (ISS) of graphite.

[0020] In some embodiments, the series of shear strain events is applied until at least 90% by weight of the graphite is exfoliated to form a distribution in the molten polymer phase of the single and multi-layer graphene nanoparticles less than 50 nm thick along the c-axis direction. In some embodiments, the series of shear strain events is applied until at least 75% by weight of the graphite is exfoliated to form a distribution in the molten polymer phase of the single and multi-layer graphene nanoparticles less than 50 nm thick along the c-axis direction. In some embodiments, the series of shear strain events is applied until at least 10% by weight, sometimes at least 20% by weight, sometimes at least 30% by weight of the graphite is exfoliated to form a distribution in the molten polymer phase of the single and multi-layer graphene nanoparticles less than 50 nm thick along the c-axis direction. The series of shear strain events is applied until at least 90% by weight of the graphite is exfoliated to form a distribution in the molten polymer phase of the single and multi-layer graphene nanoparticles less than 10 nm thick along the c-axis direction. The series of shear strain events is applied until at least 75% by weight of the graphite is exfoliated and distributed into the molten polymer phase of the single and multi-layer graphene nanoparticles less than 10 nm thick along the c-axis direction.The series of shear strain events is applied until at least 30% by weight of the graphite is exfoliated and distributed into the molten polymer phase of the single and multi-layer graphene nanoparticles less than 10 nm thick along the c-axis direction.

[0021] In some embodiments, the graphene reinforced polymer matrix composite comprises about 0.1% to about 50% graphene by weight. In some embodiments, the graphene reinforced polymer matrix composite comprises about 1% to about 30% graphene by weight. In some embodiments, the graphene reinforced polymer matrix composite comprises about 10% to about 30% graphene by weight.

[0022] In some embodiments, the reinforced polymer matrix composite comprises thermoplastic polymer chains intermolecularly crosslinked to the single-layer and multi-layer graphene nanoparticles via covalent bonds. In some embodiments, the series of shear strain events is applied until cleavages in the single-layer and multi-layer graphene nanoparticles form across the basal planes of the single-layer and multi-layer graphene nanoparticles, the edges of the cleavages comprising reactive free radicals that react with one or more of the molten thermoplastic polymers to provide a composite intermolecularly crosslinked thermoplastic polymer chains that are covalently bonded directly to the single-layer and multi-layer graphene nanoparticles.

[0023] In some embodiments, the graphite is doped with other elements to modify the surface chemistry of the exfoliated single- and multi-layer graphene nanoparticles. In some embodiments, the surface chemistry or nanostructure of the exfoliated single- and multi-layer graphene nanoparticles is modified to enhance the bond strength with the polymer matrix, increasing the strength and stiffness of the reinforced polymer matrix composite. In some embodiments, the single- and multi-layer graphene nanoparticles are directionally aligned, thereby providing one-, two-, or three-dimensional reinforcement of the polymer matrix.

[0024] The present disclosure also provides an NGS prepared according to the above method. The present disclosure further provides an article of manufacture comprising an NGS prepared according to the above method. In some embodiments, the article of manufacture can be an electrode of a battery or a capacitor. The electrode can be an anode or a cathode.

[0025] In some embodiments, the present disclosure further provides a rechargeable battery having a first electrode capable of intercalating an alkali metal, a counter electrode capable of intercalating an alkali metal, and an electrolyte comprising an organic solvent and a salt of an alkali metal in contact with the first electrode and the counter electrode, wherein the first electrode and / or the counter electrode comprises NGS prepared according to the method described above.

[0026] The foregoing and other objects, features, and advantages of the present disclosure described herein will be apparent from the following description of specific embodiments of those inventive concepts, as illustrated in the accompanying drawings, which depict only typical embodiments of the disclosure and therefore should not be considered limiting of scope. [Brief description of the drawings]

[0027] [Figure 1] 1A and 1B (collectively "FIG. 1") show examples of nano-graphite sponges (NGS) having an open-cell porous structure without metal salts (FIG. 1A) and with metal salts (FIG. 1B). [Diagram 2] Figures 2A, 2B, 2C, 2D, 2E, and 2F (collectively "Figure 2") show examples of NGS formed in different shapes. [Diagram 3] Figures 3A, 3B, and 3C (collectively "Figure 3") show an example of an NGS wire formed by winding a spiral sheet / film around a metal wire (Figure 3A). Figure 3B shows an example of an NGS wire with an insulating coating. Figure 3C is a cross-sectional view of the NGS wire shown in Figure 3B. [Figure 4] Figures 4A, 4B, and 4C (collectively "Figure 4") show examples of electrode assemblies including NGS. Figure 4A shows a cell assembly including an insulating film separating an electrode formed of NGS with a metal salt and a second electrode formed of NGS with or without a sulfide salt. Figures 4B and 4C show electrode assemblies as shown in Figure 4A, including an anode and a cathode separated by an insulating film. The electrode assemblies are formed in a brick shape (Figure 4A) and a spiral shape (Figure 4B). [Diagram 5] 5A and 5B (collectively "FIG. 5") show an example of a sandwich assembly (FIG. 5A) and an example of a prismatic cell (FIG. 5B) for use in a lithium ion battery (LIB). [Figure 6] FIG. 6 shows an exemplary process for manufacturing NGS. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] [Detailed Description of the Invention] Nanographite sponge (NGS), a three-dimensional graphene structure, has many excellent properties, including large surface area and pore volume, low density, good electrical conductivity and mechanical properties. Due to its excellent properties, NGS has great potential in various applications, such as absorbents, catalysts, catalyst supports, sensors, electrodes (e.g., transparent conductive electrodes, battery electrodes, capacitor electrodes), energy storage and conversion, fuel cells, batteries, supercapacitors, solar cells, and biological applications. One aspect of the present disclosure is directed to a novel NGS and its applications, and another aspect of the present disclosure is directed to a method for producing NGS from graphene-reinforced polymer matrix composites (G-PMCs). 1. Nanographite Sponge (NGS) The present disclosure provides a novel nano-graphite sponge (NGS) comprising graphite microparticles and graphene nanoparticles. As shown in FIG. 1A, the graphite microparticles and graphene nanoparticles form a three-dimensional (3D) interconnected, conductive open-cell porous network. Such an interconnected 3D porous network provides a large specific surface area of ​​the electrode and high electronic conductivity to the electrode assembly. The size of the open cells can range from nanometers to millimeters (e.g., 1 nm to about 10 mm). As described in the later sections, the size and structure of the pores, as well as the surface properties, are tunable by adding functional additives and / or by adjusting one or more synthesis conditions of the method for producing the NGS.

[0029] The graphite / graphene particles may comprise 50% to 100% by weight (e.g., 60%, 70%, 80%, 90%, 95%, 99% by weight) of the total weight of the NGS. In some embodiments, 5% to 90% by weight, or 10% to 80% by weight, or 10% to 70% by weight, or 10% to 60% by weight, or 10% to 50% by weight, or 10% to 40% by weight, or 10% to 30% by weight of the graphite / graphene particles are graphene nanoparticles. The graphene nanoparticles may include graphene single layer nanoparticles, few layer nanoparticles, multilayer nanoparticles, graphene flakes, and graphene platelets. The graphene nanoparticles may be in an essentially pure and uncontaminated form.

[0030] The graphite microparticles and graphene nanoparticles that make up the NGS can have different sizes. As an example, the graphene nanoparticles can have a size of 10 to 1,000 nm (e.g., 100 nm, 50 nm, 20 nm, 10 nm) thick along the c-axis direction. In other examples, at least 50% by weight (e.g., at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, at least 95% by weight) of the single-layer and multi-layer graphene nanoparticles are less than 50 nm (e.g., less than 40 nm, less than 30 nm, less than 20 nm, less than 10 nm) thick along the c-axis direction.

[0031] The NGS may further include a polymer. For example, the polymer may be a thermoplastic polymer remaining from the preparation process of the NGS. In preparing the NGS, the graphene-reinforced polymer matrix composite (G-PMC) may be subjected to a thermal annealing process that decomposes and / or gasifies some or most of the thermoplastic polymer contained in the G-PMC. The NGS may include residual thermoplastic polymer and / or carbon particles. In some embodiments, after the thermoplastic polymer is gasified, it may leave behind carbon powder resulting from its decomposition. The thermoplastic polymer, even in residual amounts, may be beneficial to the structure and function of the NGS. For example, the thermoplastic polymer may provide additional sites for functionalization in addition to those present on the graphite / graphene particles. The thermoplastic polymer also helps maintain the structural integrity of the NGS by providing additional carriers to strengthen the interactions between the graphite / graphene particles.

[0032] In some embodiments, the thermoplastic polymer may enhance the strength of the NGS by forming covalent bonds with graphene nanoparticles. As described in a later section, the NGS may be prepared from a graphene-reinforced polymer matrix composite (G-PMC). G-PMCs are prepared by in situ exfoliation of graphite in a molten thermoplastic polymer phase that includes one or more molten thermoplastic polymers. The exfoliation and distribution of graphite is performed by subjecting the molten polymer phase to a series of cleavage events, which successively exfoliate graphene with each event until the thickness of the graphene layers reaches a lower level. During this process, cleavage and separation of the exfoliated multi-layer graphene sheets occurs, generating reactive edges in the graphene sheets. Activated graphene is formed when the graphene breaks across the basal plane, providing potential sites for crosslinking to the matrix or attaching other chemically labile groups for functionalization. The reactive edges of the graphene cleavage react with and crosslink the thermoplastic polymer. Therefore, crosslinking is performed in the absence of oxygen, preferably under an inert atmosphere or vacuum, so that the reactive edges are not oxidized or otherwise non-reactive. Forming covalent bonds between the graphene and the polymer matrix significantly increases the strength of the NGS.

[0033] The NGS may be formed from a polymer composite containing nano-sized "thermosetting" graphene / polymer clusters. Each freshly exfoliated graphene sheet may form covalent bonds with one or more polymer chains. The polymer chains may then form additional covalent bonds with more freshly exfoliated graphene. These graphene sheets may form more covalent bonds with additional polymers. This process may lead to nano-sized clusters of covalently bonded graphene and polymer. These clusters have essentially similar bond structures to the thermosetting blocks of polymers whose molecules are chemically bonded together. However, unlike graphene / polymer clusters, in the thermosetting reaction, all the polymers crosslink with each other, eventually forming large crosslinked blocks, resulting in a solid mass with a strong and rigid structure. After thermosetting, the polymer loses its thermoplasticity. In contrast, graphene / polymer clusters are usually formed by local level, not global level crosslinks between graphene and polymer. Thus, only a portion of the polymer is "crosslinked" with the graphene sheets. In contrast to thermosetting, the polymer is not chemically modified and retains its thermoplasticity.

[0034] Depending on the degree of cross-linking between the thermoplastic polymer and the mechanically exfoliated graphene nanoparticles, the composite may contain one or more graphene / polymer clusters interspersed within the polymer matrix. Each graphene / polymer cluster may vary in size and shape. These graphene / polymer clusters provide structural rigidity and thermosetting properties to the newly formed composite. However, in contrast to thermosetting resins, composites containing graphene / polymer clusters retain their thermoplastic properties and can be remelted and processed into other shapes and products, just like regular thermoplastics.

[0035] The polymer may be acrylic, polymethyl methacrylate (PMMA), acrylonitrile, acrylonitrile butadiene styrene (ABS) copolymer, polyacrylonitrile (PAN), aromatic polysulfone, aromatic thermoplastic polyester, liquid crystal polymer, polyaryletherketone, polycarbonate (PC), polyetheretherketone (PEEK), polyetherimide (PEI), polyetherketone (PEK), polyethylene, polyethylene sulfide (PES), polyethylene terephthalate (PET or PETE), low density polyethylene (LDPE), high density polyethylene (HDPE), polyglycolic acid (PGA), polylactic acid (PLA), polylactic-co-glycolic acid (PLGA), polyoxymethylene It can be any one of plastics (POM / acetal), polyphenylene ether, polyphenylene oxide (PPO), polyphenylene sulfide (PPS), polypropylene (PP), polystyrene (PS), polysulfone (PSU), polytetrafluoroethylene (PTFE / TEFLONO), polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), thermoplastic elastomers, thermoplastic polyimides, ultra-high molecular weight polyethylene (UHMWPE), polyamide (PA), aliphatic polyamides, semi-aromatic polyamides, aromatic polyamides, polyamide-11 (nylon-11), polyamide-12 (nylon-12), polyamide-4,6, polyamide-6 (nylon-6), polyamide-6,10, polyamide-6,12, polyamide-6,6 (nylon-6,6), polyamide-6,9, polyamide (PA), and mixtures of two or more thereof.

[0036] The NGS may include one or more additional elements, such as Li, S, Si, Na, and combinations of two or more thereof. For example, the NGS may include one or more salts, such as sodium salts, Li salts (e.g., LiCoO2, LiMn2O4, LiFePO4, LiOH, Li2CO3, LiCl, Li2SO4, HCOOLi, CH3COOLi, Li3(C6H5O7), (COOLi)2, Li2S, Li2S2), and the like (FIG. 1B). The salts may be encapsulated within the open cells or intercalated between the graphene layers. The salt-containing NGS may be fabricated from a G-PMC containing metal salts in the composite. The salt-containing G-PMC is passed through a heat chamber to soften and liquefy the resin. After the majority of the resin is removed, an additional high temperature treatment may be performed to decompose the plastic resin. The resulting NGS includes an open-cell structure having a plurality of open cells. The cell walls consist of primary graphene, graphite, carbon particles, and / or residual plastic resin. The metal salts are encapsulated within cells surrounded by graphene / graphite walls.

[0037] Due to the unique method for preparing the NGS, as presented in a later section, the NGS can be produced in various forms / shapes by molding the G-PMC into any custom-designed size and shape. Thus, as shown in FIG. 2, the NGS can have various shapes (e.g., square, circle, triangle), sizes (e.g., centimeter, millimeter, micrometer, nanometer), or forms (e.g., rod, block, sheet, film, thread, powder). For example, the NGS can be formed into an NGS thread (FIG. 2B). In a thermal annealing process, the NGS thread can be formed by passing the G-PMC thread through a heating chamber to soften, liquefy, and / or gasify it, removing most of the plastic resin. Optionally and / or in addition, the G-PMC thread can undergo additional heat treatment to decompose the remainder of the plastic resin. During this thermal process, the plastic resin is first softened and liquefied, and then extracted from the G-PMC, leaving an open-cell sponge. Since the plastic resin is an electrical insulator, the less plastic resin remaining in the sponge, the better the electrical conductivity of the sponge. Therefore, the G-PMC sponge can be further subjected to high temperature treatment to essentially decompose most of the plastic resin, further reducing the amount of plastic resin in the sponge. Carbon particles from the decomposed resin remain in the sponge. The graphene and the remaining plastic resin provide the strength and structural integrity of the sponge. The amount of remaining plastic resin can be controlled by adjusting the heat treatment process, for example, the graphite / plastic resin ratio.

[0038] The size of the open cells can be as small as nano-sized bubbles and as large as 10 mm sized bubbles. The presence of the nano-sized bubbles increases the surface area of ​​the sponge. The size of the open cells can be adjusted by adjusting one or more conditions for preparing the NGS, such as the initial resin / graphite mixing ratio. The higher the resin / graphite ratio, the larger the size of the open cells. This is because in a graphene-polymer matrix with a high resin / graphite ratio, the graphite / graphene particles are more sparsely distributed, which increases the size of the open cells of the NGS. The ability to adjust the size of the open cells of the NGS is particularly advantageous, since the NGS can be customized for various applications. For example, if the NGS needs to be functionalized or other elements such as lithium, sulfur, or sodium salts need to be inserted, a larger size of the open cells is beneficial. On the other hand, the smaller the size of the open cells, the larger the surface area of ​​the NGS. NGS with a larger surface area is a better electrical conductor. The large surface area of ​​NGS is also beneficial when it is used as a gas or liquid absorbent, for example, NGS with its large surface area can be used to remove organic contaminants or oil spills from water.

[0039] The NGS threads may have diameters ranging from about 1 μm to about 10 mm. The threads may be further formed into other three-dimensional configurations (Figure 2). For example, multiple NGS threads may be bundled or woven together to form larger NGS bundles (Figure 2C). The NGS bundles may be twisted together to form sponge ropes that are stronger against accidental breakage. The NGS threads / bundles / ropes may be coated with protective coatings such as insulating or plastic coatings to insulate electricity and facilitate transportation and manipulation. Graphite is a conductive material and graphene is more conductive than copper, so it may be used as a wire / cable to transmit electricity. This is also because in the sponge structure, both graphite and graphene form the cell walls and provide contact surfaces for electrical conductivity. Nano-sized bubbles increase the surface area of ​​the walls, increasing electrical conductivity and improving the charging speed of the battery. Graphene is also known to be a mechanically strong material (over 200 times stronger than steel). The NGS wires / cables have excellent electrical conductivity but a lower mass density than metal wires / cables (e.g., copper / aluminum wires / cables). Importantly, as described in a later section, the strength and conductivity of the NGS can be customized, for example, by controlling the degree of exfoliation of graphite into graphene.

[0040] The NGS may also be manufactured into a fine powder grade. The powder form may have a size ranging from about 0.1 μm to about 100 μm. The powder form of NGS may be prepared by extruding thin NGS threads. The NGS threads may first be divided into small pellets. The pellets may have a length ranging from about 1 μm to about 10 mm. The NGS pellets may undergo a grinding process to obtain a micro powder form of the NGS. The powder size may be controlled by the degree of grinding. The ground NGS powder may be further separated in an air chamber to isolate ultra-micro particles from the bulk. This process may control the minimum size of the powder. It may also facilitate an air filtration system to remove particles in the air and prevent the inhalation of ultra-fine powder by workers. Also, NGS powder with graphene / graphite / carbon powder / residual resin may be used instead of pre-exfoliated graphene powder. It is less expensive and eliminates the potential health hazards of inhaling pre-exfoliated graphene powder.

[0041] The powder form of NGS can be used to create a suspension / solution by mixing NGS power with a liquid carrier. The suspension / solution can be used to modify the surface properties of a substrate. For example, the suspension / solution can be printed onto the surface of the substrate. Due to the electrical and thermal conductivity of NGS, substrates with NGS printed onto them can be used in vehicles to eliminate static charge, electrically heated surfaces, and other power transfer applications. For example, the suspension / solution can also be used with lithium salts to coat aluminum foil to form the anode of a battery.

[0042] The graphene sponge powder consists of highly exfoliated graphene with residual graphite, residual plastic resin, and / or carbon powder. It can be used as a low-cost alternative to pre-exfoliated graphene. The graphene sponge powder can be mixed into paints to improve corrosion resistance. It can be mixed into carriers to coat lithium salts for use as anodes in secondary batteries. It can also be coated into flat panels to be used as heating boards for home and clothing heaters.

[0043] The disclosed NGS may be fused with a metal to form an NGS / metal hybrid material (FIG. 3). For example, the NGS wire / cable described above may be a metal / NGS hybrid wire / cable. Such an NGS / metal hybrid wire / cable not only exhibits reduced resistivity, but also improved elasticity and current resistance. Furthermore, the NGS / metal hybrid wire / cable has a reduced mass density compared to a copper wire / cable. The metal may include any metal suitable for use as a medium for transmitting electrical current, such as aluminum, copper, gold, platinum, silver, iron, etc. The metal may also include metal alloys, such as alloys of aluminum, copper, gold, platinum, silver, iron, etc. Similarly, the NGS film may be fused with a metal to form an NGS / metal hybrid film. Similar to the NGS / metal hybrid wire / cable, such an NGS / metal hybrid film exhibits both high electrical conductivity and high elasticity. Due to these advantages, the NGS / metal hybrid film may be manufactured in a thin thickness, for example, between about 1 μm and about 10 mm.

[0044] Previous attempts to mix pre-exfoliated graphene into metals such as aluminum to produce lightweight electrical wires with high electrical conductivity have faced several difficulties. First, existing methods can only load very limited amounts of graphene into metals, similar to mixing pre-exfoliated graphene into plastic resins. Second, it is difficult to control the distribution of graphene in the metal, and thus many areas of the mixture have little or no graphene remaining. Third, the incompatibility between graphene and metals has made it more difficult to distribute graphene in the metal.

[0045] The sponge yarns described herein offer a solution to this problem. The high concentration of graphene is interconnected within the sponge, making it more capable of conducting electricity than copper. The graphene sponge threads are further reinforced with a metal, such as aluminum, making them stronger and less susceptible to mechanical forces. At the same time, the metal-reinforced NGS wires offer better electrical conductivity, better durability and strength, and lower weight density than typical metal wires.

[0046] Therefore, it is advantageous to use NGS as the starting material for preparing the NGS / metal hybrid material. This is because NGS, such as the NGS thread, has open cells with no internal volume. The sponge can be impregnated with metal by immersion in a tank of molten metal. The sponge thread is then drawn through a hole. The diameter of the hole is slightly larger than the diameter of the thread, controlling the diameter of the thread of the metal-coated sponge. The metal can be aluminum, alloy, or other low melting point metal. The metal reinforces the sponge thread and improves electrical conductivity. The thicker the outer metal layer, the stronger the sponge thread. The electricity can pass through the graphene and graphite of the sponge thread and the impregnated metal. The metal-impregnated NGS thread can be further coated with an insulating outer coating so that the NGS thread can be used as an electrical wire (FIG. 3B and FIG. 3C). The resulting NGS wire is lighter than copper wire.

[0047] NGS can also be formed into thin sheet / film form by extruding G-PMC into a sheet (FIG. 2D), which can be stretched into even thinner sheets or films. It can also be made into thin films by extrusion blow molding (EBM). The thin sheet / film can then be processed in a heated chamber to expel the plastic resin from the sheet / film, resulting in an open-cell NGS sheet / film. The thickness of the sheet or film can range from 0.001 mm to 10 mm (FIG. 2D). The thinner the gauge of the sheet / film, the easier it is to remove the resin from the sponge. The NGS sheet / film can include graphene / graphite particles with or without residual plastic resin. In some embodiments, the NGS sheet / film can further include carbon particles resulting from the decomposition of the thermoplastic polymer during the thermal process. Compared to other forms of NGS, the plastic resin can be easily and quickly removed from the thin sheet / film.

[0048] As described above, the salt-containing NGS sheet / film can be produced from the salt-containing G-PMC after the resin has been drained from the composite. The resulting NGS sheet / film can comprise graphene / graphite / residual resin / metal salt or graphene / graphite / residual resin / carbon particles / metal salt. The size of the open cells can be adjusted by varying the initial resin / graphite ratio. The higher the resin / graphite ratio, the greater the cell size. The metal salt is enclosed in cells and surrounded by cell walls composed of graphene / graphite / carbon particles / residual resin.

[0049] The NGS sheet / film may be wound up into a continuous roll (Figure 2E). The sponge sheet / film may be spirally wound into a continuous tube with a hollow center of 0.01 mm to 10 mm in diameter (Figure 2F). The sponge spiral wound tube may be manufactured with a single layer sheet / film or a multi-layer sheet / film. The tube structure increases the resistance of the sheet / film to bending / tearing / damage and protects the electrical conductivity without interruption. The sponge spiral wound tube may be further strengthened by having a metal wire in the center (Figure 3A). The metal may be copper, aluminum, steel or other alloys. The metal wire provides tensile strength to the spiral tube and resists breakage and other damages, although it adds slightly to the weight of the tube. The sponge tube may be wrapped with an insulating outer layer to make it into an electrical wire (Figure 3B and Figure 3C). It is more flexible and durable to breakage / cracks while maintaining continuity to conduct electrical power. It is light weight and highly conductive, serving as an alternative to copper / aluminum wires / cables. Moreover, graphene sponge hollow spiral tubes coated with a protective outer layer can be efficient heat exchangers: for example, a fluid, either gas or liquid, can flow through the tube, transferring heat to or from the surrounding environment.

[0050] The metal-containing NGS sheet / film according to FIG. 4 can be paired with another NGS sheet / film, separated by an insulating film, and then folded once or multiple times and filled with a liquid transport medium to form a compact-sized rechargeable battery with high-density charge capacity and fast charging speed. The graphene and graphite are highly conductive, so aluminum or copper foil is not required as the anode and cathode conductors (FIG. 4). In the anode, the open cells hold a large amount of metal ions. The high level of graphene content ensures good electrical contact with the metal ions. Thus, the metal ions can be charged and discharged. In the cathode, the open cells have a huge contact surface for the metal ions held by the graphite in the cells. The open cells provide a large space to accommodate the expansion and contraction of the metal ions during the charge and discharge phases. Moreover, the open cells allow the metal ions to be held within the cells without causing dendrite growth, thus extending the service life of the rechargeable battery (FIG. 5).

[0051] 1.1. Graphene batteries and supercapacitors Due to the high electrical conductivity, 3D porous structure, high electrochemical stability, and high elasticity and mechanical stability of the interconnected network, NGS is an attractive material for applications in the fields of energy storage and conversion, such as batteries, supercapacitors, fuel cells, solar cells, etc. The present disclosure provides a product comprising the above NGS. The product can be a battery (e.g., graphene battery, lithium ion battery, graphene-lithium-sulfur battery) or a capacitor (e.g., supercapacitor) or a part thereof. For example, the NGS can be used to form an electrode (e.g., anode, cathode). In some embodiments, the present disclosure further provides a rechargeable battery containing NGS, which can be used in common everyday products such as mobile devices, electric vehicles (EVs), hybrid electric vehicles (HEVs), or smart energy systems. Rechargeable batteries containing NGS allow for shorter cycle times and improved electrode density. They also have the ability to hold a charge longer, extending the life of the battery.

[0052] The secondary battery is composed of an anode, a cathode, one or more insulating layers, and a conductive medium. The conductive medium may be an electrolyte including an organic solvent and an alkali metal salt in contact with the anode and the cathode. The anode may be intercalated with an alkali metal that may be enclosed in the open cells and in contact with the graphene / graphite walls.

[0053] The anode may be made of a sponge-like sheet / film (e.g., NGS sheet / film) as described above. For example, the anode may be made of an NGS sheet / film containing graphene / graphite / carbon particles / resin residue / metal salt. The NGS sheet / film has an open-cell structure and is highly conductive. The cell size ranges from nanometer size to millimeter size. The cell walls consist of a graphene / graphite / resin residue mixture, where the graphene provides the sponge structure and the resin increases its flexibility. The NGS sheet / film may be covered with an insulating layer coating / cover. It is then folded with the opposite NGS sheet / film to form the cathode and anode. A conductive medium is introduced to fill all the open cells of the NGS. This assembly constitutes a rechargeable battery. During charging or discharging, metal ions (e.g., lithium, sulfur, sodium) pass through the insulating coating between the cathode and anode, and energy is stored or discharged. In this NGS battery configuration, copper or aluminum is not required as a conductor. As a result, the weight of the battery is significantly reduced. Such pure NGS electrodes are also possible due to the excellent mechanical rigidity of NGS. The graphene sponge structure has a large contact surface area with the metal salt, so it can accommodate more salt in a specific volume, resulting in higher power density. Also, graphene / graphite is a highly conductive material, so it can accommodate high current charging and discharging. This shortens the charging time of rechargeable batteries. Furthermore, since the metal salt is encapsulated in the open cells, the hollow spaces of the cells can accommodate the expansion and contraction of the metal salt. Therefore, the NGS battery can inhibit destructive dendrite growth and extend the battery life. The application of NGS in batteries will be discussed in detail in the next section.

[0054] For lithium-sulfur batteries, the use of graphene as a support material for sulfur ions eliminates some of the problems associated with sulfur batteries thanks to its unique properties such as large surface area, high chemical / thermal stability, good mechanical strength and high electrical conductivity. The high surface area provides good dispersion of sulfur, controls the migration of sulfur ions and eliminates the accumulation of sulfur ions in the cathode. The one-pot synthesis described in this disclosure can also be used to produce graphene-supported sulfur particles.

[0055] NGS-containing batteries are available in many forms. FIG. 5A shows an example of an NGS-containing rechargeable battery. To form a rechargeable foam, the anode is combined with other elements to form a layered or "sandwich" structure, as generally shown in FIG. 5A. Thus, the NGS sponge anode 120 is assembled with an electrochemically active cathode or counter electrode 150 that can reversibly incorporate lithium. The counter electrode 150 can incorporate a particulate material that is lithium intercalable or otherwise capable of reacting reversibly with lithium. The particulate material is disposed on a sheet-like conductive cathode current collector 160. The particulate lithium intercalable cathode material can be a transition metal chalcogenide. Preferred compositions include conventional lithium ion battery (LIB) cathode materials, such as molybdenum sulfide, vanadium oxide, manganese oxide, and the like. The particulate cathode material can be distributed on the sheet-like current collector 160 by a slurrying and coating process conventional for LIBs. A sheet-like porous, electrically insulating separator 140 , which can be microporous polypropylene or a polymer mesh, is inserted between the anode 120 and the cathode 150 .

[0056] In some configurations, a lithium metal sheet is disposed between the anode 120 and the separator 140 such that the lithium sheet is adjacent to and in contact with the anode 120. The size of the lithium metal sheet 130 may be selected such that the surface of the sheet is coextensive with the surface of the anode 120, and the thickness of the sheet 130 is selected such that the correct amount of lithium is present for the insertion reaction, as discussed below. The sandwich structure 100 may further include an additional separator 170 disposed on the cathode current collector 160. This sandwich structure may be used to construct various battery configurations (e.g., spiral / cylindrical cell, prismatic cell, pouch cell, button cell), an example of a prismatic cell is shown in FIG. 5B.

[0057] An electrolyte, preferably comprising a lithium salt or other lithium-containing compound dispersed in a suitable organic solvent and compatible with both the cathode and anode materials, is used in the foam. An electrolyte solvent capable of wetting the separator and particulate matter is desirable. The electrolyte solvent may include ester solvents such as propylene carbonate (PC), ethylene carbonate (EC), or mixtures thereof. Examples of other solvents that may be used may include, but are not limited to, 2-methyltetrahydrofuran (2-MTHF), tetrahydrofuran, sulfolane, dimethylsulfite, monoglyme (1,2-dimethoxyethane), diglyme, triglyme, tetraglyme, p-dioxane, 1,3-dioxane, dimethoxymethane, diethyl ether, and trimethoxyethane. Suitable electrolyte salts may include, but are not limited to, LiAsF6, LiPF6, LiClO4, LiBF4, LiB(C6H5)4, LiCF3F, LiAlCl4, LiBr, and mixtures thereof.

[0058] Since the lithium metal has a higher electrochemical potential than the anode, the addition of electrolyte to the bubble causes the lithium metal in the sheet 130 to intercalate into the carbonaceous composition of the anode 120. In effect, the anode 120 and lithium sheet 130 constitute a temporary bubble with a carbonaceous electrode and a lithium electrode. Because the sheet 130 is electrically and physically connected to the anode 120, the temporary bubble is short-circuited. As a result, the temporary bubble discharges and lithium passes from the high potential electrode (sheet 130) to the low potential electrode (anode 120). This initial lithiation process can be carried out at or below about room temperature (20° C.). The initial lithiation process occurs when the lithium metal in the sheet 130 is charged to the carbonaceous composition of the anode 120 by charging the Li x This continues until the anode 120 is completely consumed by the carbon in the formation of C6 or until the anode 120 is saturated with lithium, whichever occurs first.

[0059] In addition to rechargeable batteries, NGS may be used to fabricate graphene supercapacitors (e.g., double-layer capacitors, pseudocapacitors). Supercapacitors are useful electrochemical energy storage devices that are typically used as sustainable power sources because they have higher power density than batteries and higher energy density and longer life cycles than traditional dielectric capacitors (e.g., electric vehicles and mobile electronic devices). Supercapacitors store energy by accumulating charge at the interface of the electrode and electrolyte through polarization. Activated carbon has traditionally been used as an electrode material, but its main drawback is that it cannot operate at high voltages. Graphene and its derivatives are useful due to their open-pore structure, high electrical conductivity, high specific surface area, feasibility of production, and low cost; all of which are desirable attributes for supercapacitors. However, graphene sheets tend to form irreversible aggregates due to strong π-π stacking and van der Waals interactions unless they are well separated from each other. Meanwhile, the electrochemical binders and additives are usually required to fabricate graphene-based electrodes, which adversely affect the specific capacitance of the resulting electrodes. Due to these challenges faced by 2D graphene, 3D porous NGS with high electrical conductivity and large specific surface area, short diffusion paths for electrolyte ions and fast transport channels for electrons are ideal supercapacitor materials.

[0060] NGS can also be used in fuel cells, as a catalyst or catalyst support to support metals and alloys in oxidation. Compared to 2D graphene sheets, NGS has a larger active surface area for electron / ion transport. The uniformity of the graphene surface of NGS also eliminates agglomeration and promotes uniform distribution of platinum particles throughout the support. NGS can be doped with nitrogen after nitrogen plasma treatment. Doped NGS has nitrogen-based functional groups on its surface, allowing for better dispersion and decoration with platinum nanoparticles. Doping NGS with nitrogen improves its electrical conductivity and electrocatalytic activity.

[0061] 1.2. Other Uses 1.2.1. Catalysts and catalyst supports NGS can be used as a graphene-based catalyst. It can be used in organic synthesis, sensors, environmental protection, and energy-related systems. NGS overcomes the drawbacks associated with traditional graphene-based catalysts, such as the large resistance due to structural defects and the strong planar stacking of graphene sheets, which greatly reduces the properties. The 3D porous interconnected network of NGS is beneficial for the diffusion and migration rate of ions, providing a special reaction microenvironment and conductive multiplexed pathways for rapid charge transfer and conduction. NGS is desirable for use as a metal-free catalyst or as a rigid matrix to accommodate metals, metal oxides, and catalyst precursors for applications in many catalytic systems.

[0062] NGS can be used as a catalyst support. The 3D porous structure of NGS facilitates mass transfer and maximizes access to the catalyst surface. Therefore, NGS is ideal for supporting catalytically active materials. The ease of catalyst separation, high turnover rate, low catalyst loading, and recyclability make NGS applicable in industrial environments.

[0063] 1.2.2. Sensors and biological applications Due to their low mass density, large surface area, good mechanical stability, and high electrical conductivity, NGS can be used in biosensors and gas sensing devices. 3D structures NGS are suitable for housing drugs, biomolecules, bacteria, and even cells, resembling the 3D environment in vivo. For example, NGS can be used as nanocarriers to deliver therapeutic drugs such as anticancer drugs.

[0064] 2. Preparation of nanographite sponge (NGS) Although several methods have been disclosed, preparing highly ordered graphene-based materials such as NGS remains very challenging. Thus, one of the objectives of the present disclosure is to provide a method for the fabrication of said NGS from graphene-reinforced polymer matrix composites (G-PMCs). Referring now to FIG. 6, G-PMCs are prepared by a polymer processing method involving in situ exfoliation of well-crystallized graphite particles dispersed in a molten thermoplastic polymer matrix (601). From the graphene-reinforced polymer matrix composites, a molded shape can be formed using a typical plastic molding process (602). The molded part is then placed in an oven in a "soft mold" of sand or other ceramic particles and slowly heated in the oven until the polymer decomposes and gasifies (603). For example, the heating temperature can be raised to or near the Tg (gasification temperature) of the polymer for a sufficient time (e.g., 20 hours) to gasify or decompose the polymer. The heating process can be carried out in a high pressure or low pressure environment (e.g., vacuum). In some embodiments, the heating process can also be carried out in an inert gas atmosphere. For example, a graphene-reinforced polymer matrix composite may be heated in an oven chamber filled with nitrogen or argon gas. In some embodiments, the heating temperature may be increased to or near the Tm (melting temperature) of the polymer for a period of time (e.g., 20 hours) before the temperature is increased to the Tg. In one example, a graphene-reinforced PA 6-6 polymer matrix composite was first heated at about 62°C for about 20 hours, then heated at about 262°C for about 20 hours. In another example, a graphene-reinforced PEEK polymer matrix composite was first heated at about 200°C for about 20 hours, then heated at about 280°C for about 20 hours. The resulting G-PMC is converted to NGS by heating the composite until the polymer liquefies and gasifies in a controlled atmosphere (604) at a temperature and duration sufficient to decompose and gasify the polymer. In some conditions, to prepare NGS for use in electrodes, the composition of the NGS is further modified by vapor or liquid infiltration of electroactive elements using organometallic or inorganic precursors (605).

[0065] The polymers used as a medium to effect exfoliation within the system, and potential additives, may leave materials useful in terms of attaching lithium or other ions such as silicon, sodium, or sulfur. Examples of polymers containing these atoms include, but are not limited to, polydimethylsiloxane, polyphenylene sulfide, and sodium polyacrylate. Silica, sodium-containing powders, or sulfur powders may be added prior to exfoliating the graphite or just prior to the final step of mixing the polymer-graphite composite.

[0066] The sponge has a huge internal surface area for contact with the electrolyte, allowing for large current draw. The sponge itself is open-cell shaped and can have a large volume, although the size of the achievable dendrite volume is limited. The mechanical properties of graphene provide a nanocarbon sponge that inhibits the collapse due to volume changes of the electrode and the growth of large dendrites during charge / discharge cycles, thereby extending the life of high-performance LIBs.

[0067] In one aspect, the present disclosure provides a method for forming a nano-graphite sponge, the method comprising: (a) distributing graphite microparticles into a molten thermoplastic polymer phase; (b) applying a series of shear strain events to the molten polymer phase, whereby the molten polymer phase successively exfoliates graphite with each event until at least 1 wt%, optionally at least 5 wt%, optionally at least 10 wt%, optionally at least 20 wt%, optionally at least 50 wt%, optionally at least 75 wt%, optionally at least 95 wt% of the graphite is exfoliated, forming a distribution in the molten polymer phase of single and multi-layer graphene nanoparticles less than 50 nm thick along the c-axis direction, thereby forming a graphene-reinforced polymer matrix composite; and (c) heating the graphene-reinforced polymer matrix composite until the polymer decomposes and gasifies to form a nano-graphite sponge. In some embodiments, the method further comprises (d) vapor or liquid infiltrating a precursor comprising an electroactive element into the nano-graphite sponge to form a nano-graphite sponge intercalated with an electroactive element.

[0068] In some embodiments, the method further comprises forming a uniform distribution of one or more additives in the molten polymer phase. The additives facilitate the intercalation of the electroactive elements into the nano-graphite sponge. The additives may be added before exfoliating the graphite or just prior to the final step of mixing the polymer-graphite composite. Examples of the additives may include, but are not limited to, titanium, sulfur, silica and silicates, phosphorus, lithium, and aluminum-based silicates.

[0069] 3. Preparation of graphene-reinforced polymer matrix (G-PMC) This disclosure describes a highly efficient mixing method for converting polymer composites containing well-crystallized graphite particles into nano-dispersed single- or multi-layer graphene particles from which the NGS are formed. The method involves in-situ exfoliation of graphite layers by compounding in a batch mixer or extruder that imparts repeated high shear strain rates. In both processes, extended mixing times promote the exfoliation of graphite into graphene nanoparticles within the polymer matrix composite (PMC). Additionally, additives may be used to promote sufficient graphene / polymer bonding, thereby producing graphene-reinforced polymer matrix composites (G-PMCs). The method produces G-PMCs at low cost that offer many property advantages, including enhanced specific stiffness and strength, improved electrical / thermal conductivity, and retained optical transparency.

[0070] Repeated blending during batch mixing processes or single-screw extrusion is used to gradually convert the initial graphite particle dispersion into a uniform nano-dispersion of individual graphene nanoparticles. In some conditions, an inert gas or vacuum may be used during processing. This method is described herein as "mechanical" exfoliation to distinguish it from the "chemical" exfoliation that is the primary driver of much of the research today. The advantage of the mechanical method is that a contaminant-free graphene-polymer interface is formed during high shear mixing, thus ensuring good interfacial adhesion or bonding. Another advantage of in situ exfoliation is that it avoids the creation and manipulation of graphene flakes and disperses them uniformly in the polymer matrix phase.

[0071] Depending on the number of shear strain events in the system, the method provides multilayer graphene, graphene flakes, graphene platelets, few-layer graphene, or single-layer graphene in pure and uncontaminated form. Platelets have diamond-like stiffness and are used in polymer reinforcement. Graphene in all forms acts as a polymer reinforcement, inhibiting crack propagation and thereby increasing the toughness of the polymer. Graphene can be used as an additive to polymers and other compositions to provide electrical and thermal conductivity. The thermal conductivity of graphene makes it a desirable additive for thermal management in electronic devices and lasers.

[0072] The graphene may be produced as a graphene-polymer mixture suitable for use as is as a G-PMC which may be pelletized by conventional means for further manufacturing processing. Alternatively, a higher concentration of graphite may be used initially to provide a concentrated form of a graphene-polymer masterbatch which may also be pelletized and then used to add the graphene as a reinforcing agent to a polymer composition. As a further alternative, the graphene may be separated from the polymer, for example by combustion or selective dissolution, to provide particles of essentially pure graphene.

[0073] The availability of graphite-rich mineral deposits, containing relatively high concentrations (e.g., about 20%) of well-crystallized graphite, represents a low-cost, virtually inexhaustible source of raw material. As described below, the extraction of graphite particles from mined materials can be cost-effectively accomplished. Synthetic graphite (such as pyrolytic graphite) of high purity and excellent crystallinity can also be used for the same purpose. In this case, however, the exfoliation process induced by batch mixing or extrusion compounding produces a laminated composite material in which the graphene nanoparticles are oriented over relatively large areas. Such laminated composite materials may be suitable for certain applications.

[0074] Mechanical exfoliation of graphite within a polymer matrix can be achieved by polymer processing techniques that impart repeated high shear strain events to mechanically exfoliate graphite microparticles into multi-layer or single-layer graphene nanoparticles within the polymer matrix.

[0075] A series of shear strain events is defined as subjecting the molten polymer to an alternating series of higher and lower shear strain rates over essentially the same time interval, resulting in the application of a series of pulsating, higher and lower shear forces associated with the shear strain rates to the graphite particles in the molten polymer. The higher and lower shear strain rates are defined as a first higher shear strain rate that is at least twice as large as the second lower shear strain rate. The first shear strain rate is in the range of 100-10,000 s-1. At least 1,000-10,000,000 alternating pulses of higher and lower shear strain pulses are applied to the molten polymer to form exfoliated graphene nanoparticles. The number of alternating pulses required to exfoliate graphite particles into graphene particles may depend on the dimensions of the original graphite particles at the start of the process, i.e., smaller original graphite particles may require fewer alternating pulses to reach graphene than larger original graphite particles, which can be readily determined by one of ordinary skill in the art guided by this specification without undue experimentation.

[0076] In some embodiments, the method includes applying a series of shear strain events for 1000 seconds. -1 Less than or equal to (for example, 1000 seconds -1 , 900 seconds -1 , 800 seconds -1 , 700 seconds -1 , 600 seconds -1 , 500 seconds -1 , 400 seconds -1 , 300 seconds -1 , 200 seconds -1 , 100 seconds -1 , 50 seconds -1 ) shear rate.

[0077] After high shear mixing, the graphene flakes are uniformly dispersed in the molten polymer, randomly oriented, and have a high aspect ratio. The orientation of the graphene can be achieved in many different ways. Conventional drawing, rolling, and extrusion methods can be used to directionally align the graphene within PMC fibers, filaments, ribbons, sheets, or other elongated shapes. The method for producing and characterizing G-PMCs consists of four major steps, including: 1. Extraction of crystalline graphite particles from mineral sources; 2. The incorporation of extracted graphite particles into the polymer matrix phase and the transformation of graphite-containing polymers into graphene-reinforced polymer matrix composites (G-PMCs) through a highly efficient mixing / exfoliation process; 3. Morphological analysis to determine the degree of mechanical exfoliation and distribution of multi-layer graphene and graphene nanoparticles; and 4. X-ray diffraction analysis to determine multilayer graphene or graphene crystallite size as a function of mechanical exfoliation.

[0078] Highly crystalline graphite can be extracted from graphite ore by a multi-step process, as described below.

[0079] 1. Crushing: Bars of graphite ore excavated from a mine can be crushed by placing them in a vice.

[0080] 2. Grinding: The crushed graphite ore is ground in a mortar and pestle.

[0081] 3. Size reduction: The crushed graphite ore may be put into a sieve with a mesh size of 1 mm to reduce the size. The larger pieces that do not pass through the screen may be crushed in a mortar and pestle and then reduced in size again to 1 mm mesh size. Finally, all the material passes through the 1 mm mesh size to obtain graphite ore powder.

[0082] 4. Density separation with water: Powders of 1 mm size can be placed in a column filled with water and stirred until a clear separation is formed between the denser and less dense parts of the solid. Graphite has a density of water (1 g / cm 3 ), whereas silicon is much denser (2.33 g / cm 3 The top material is siphoned off along with the water and then dried. The dry powdered graphite is called separated mineral graphite (SMG).

[0083] In commercial practice, very large crushers and grinders are available which produce tonnages of mixed powder from which the graphite component can be separated by standard flotation techniques.

[0084] Thus, an in situ exfoliation method for producing G-PMC is provided. In this method, a polymer homogeneously blended with micron-sized crystalline graphite particles is subjected to repeated compounding steps during batch mixing or extrusion at a temperature at which the polymer adheres to the graphite particles. Typical polymers have a thermal viscosity (without graphite) of over 100 cps at compounding temperatures. Compounding temperatures vary from room temperature (for polymers that melt at room temperature) to 600°C depending on the polymer. Typical compounding temperatures range from 180°C to 400°C.

[0085] In one embodiment, the extrusion compounding element is as described in U.S. Pat. No. 6,962,431, the disclosure of which is incorporated herein by reference, and has a compounding section known as an axially grooved extensional mixing element or a helically grooved expansional mixing element. The compounding section acts to elongate the polymer and graphite streams, which then undergo repeated folding and stretching of the material. This provides excellent distributive mixing, which results in the gradual exfoliation of the graphite particles into individual graphene nanoparticles. A batch mixer may also be equipped with equivalent mixing elements. In some embodiments, a standard type injection molding machine is modified to replace the standard screw with a compounding screw for the purpose of compounding the materials as the composition is injection molded. Such an apparatus is disclosed in U.S. Patent Application Publication No. 2013 / 0072627, the disclosure of which is incorporated herein by reference in its entirety.

[0086] Thus, the effect of each compounding pass is to shear the graphene layers one after the other so that the original graphite particles are gradually transformed into a very large number of graphene nanoparticles. After a suitable number of said passes, the end result is a uniform dispersion of discrete graphene nanoparticles in the polymer matrix phase. Longer mixing times or more passes through the compounding elements will reduce the graphite crystal size and promote the exfoliation of the graphite into graphene nanoparticles within the polymer matrix; however, the shearing events must not be of such duration as to degrade the polymer.

[0087] As the graphene nanoparticle content increases during multi-pass extrusion, the viscosity of the polymer matrix increases due to the effect of an increasing number of polymer / graphene interfaces. To ensure continued refinement of the composite structure, the extrusion parameters are adjusted to compensate for the higher viscosity of the composite.

[0088] Automated extrusion systems are available to subject the composite to as many passes as required, using mixing elements such as those described in U.S. Patent No. 6,962,431, with a recirculation stream to return the flow to the extruder input. The processing of graphene-reinforced PMCs is straightforward, and there is no manipulation of the graphene particles, resulting in low production costs.

[0089] To mechanically exfoliate graphite into multilayer graphene and / or single layer graphene, the shear strain rate induced in the polymer during processing must increase the shear stress in the graphite particles above the critical stress or interlaminar shear strength (ISS) required to separate two layers of graphite. The shear strain rate in the polymer is controlled by the type of polymer and processing parameters such as mixer geometry, processing temperature, and revolutions per minute (RPM).

[0090] At a constant temperature, the shear strain rate (γ & The processing temperature and speed (RPM) required for a particular polymer can be determined from polymer rheology data, considering that ) depends linearly on RPM as shown in Equation 1. The mixer geometry is expressed as the radius of the rotor, r, and the space between the rotor and the barrel, Δr.

[0091] Equation 1: γ & =(2πr / Δr)(RPM / 60) Polymer rheology data collected for a particular polymer at three different temperatures provides a log shear stress vs. log shear strain rate graph. The ISS of graphite ranges from 0.2MPa to 7GPa, but the novel method quantified the ISS at 0.14GPa. Thus, the required processing temperature, shear strain rate, and RPM can be determined for a particular polymer from the log shear stress vs. log shear strain rate graph collected for the polymer at a constant temperature, so that the shear stress in the polymer is equal to or greater than the ISS of the graphite to mechanically exfoliate the graphite in the polymer matrix during processing. Under normal processing conditions, the polymer has enough surface energy to behave like the sticky side of an adhesive tape, so that shear stress can be shared between the polymer melt and the graphite particles.

[0092] The G-PMC from which the NGS is formed is then formed by distributing the graphite microparticles into a molten thermoplastic polymer phase, and applying a series of shear strain events to the molten polymer phase such that the molten polymer phase successively exfoliates the graphite with each event until at least 1 wt%, optionally at least 5 wt%, optionally at least 10 wt%, optionally at least 20 wt%, optionally at least 50 wt%, optionally at least 75 wt%, and optionally at least 95 wt% of the graphite is exfoliated to form a distribution in the molten polymer phase of single-layer and multi-layer graphene nanoparticles less than 50 nm thick along the c-axis direction. In some embodiments, the series of shear strain events can be applied until at least 50 wt% of the graphite is exfoliated to form a distribution in the molten polymer phase of single-layer and multi-layer graphene nanoparticles less than 50 nm thick along the c-axis direction. In some embodiments, the series of shear strain events can be applied until at least 75 wt% of the graphite is exfoliated to form a distribution in the molten polymer phase of single-layer and multi-layer graphene nanoparticles less than 50 nm thick along the c-axis direction.

[0093] In some embodiments, the series of shear strain events may be applied until at least 90% by weight of the graphite has exfoliated to form a distribution in the molten polymer phase of single-layer and multi-layer graphene nanoparticles less than 50 nm thick along the c-axis direction. In some embodiments, the series of shear strain events may be applied until at least 50% by weight of the graphite has exfoliated to form a distribution in the molten polymer phase of single-layer and multi-layer graphene nanoparticles less than 10 nm thick along the c-axis direction. In some embodiments, the series of shear strain events may be applied until at least 75% by weight of the graphite has exfoliated to form a distribution in the molten polymer phase of single-layer and multi-layer graphene nanoparticles less than 10 nm thick along the c-axis direction. In some embodiments, the series of shear strain events may be applied until at least 90% by weight of the graphite has exfoliated to form a distribution in the molten polymer phase of single-layer and multi-layer graphene nanoparticles less than 10 nm thick along the c-axis direction.

[0094] Graphene reinforced polymer matrix composites suitable for use in the present invention comprise an essentially uniform distribution in a thermoplastic polymer matrix of about 5% to about 50% by weight of the total composite weight of particles selected from the group consisting of graphite microparticles, single layer graphene nanoparticles, multilayer graphene nanoparticles, and combinations of two or more thereof, wherein at least 50% by weight of the particles consist of single layer and / or multilayer graphene nanoparticles less than 50 nm thick along the c-axis direction.

[0095] According to some embodiments, the graphene reinforced polymer matrix composite comprises an essentially uniform distribution of between about 1% and about 50% by weight of the total composite weight of graphite and graphene particles. In some embodiments, the graphene reinforced polymer matrix composite comprises between about 4% and about 40% by weight of the total composite weight of graphite and graphene particles. In some embodiments, the graphene reinforced polymer matrix composite comprises between about 6% and about 30% by weight of the total composite weight of graphite and graphene particles. In some embodiments, the graphene reinforced polymer matrix composite comprises between about 8% and about 20% by weight of the total composite weight of graphite and graphene particles.

[0096] Graphene-reinforced polymers according to the present disclosure typically contain between about 0.1% and about 50% graphene by weight. In some embodiments, the polymer contains between about 1.0% and about 30% graphene by weight. In some embodiments, the polymer contains between about 1.0% and about 10% graphene by weight. Polymer masterbatches typically contain between about 5% and about 50% graphene by weight, and more typically between about 10% and about 30% graphene by weight.

[0097] As defined herein, "essentially uniform" means that the graphene particles are sufficiently distributed throughout the molten thermoplastic polymer phase such that individual aliquots of the composite contain the same amount of graphene within about 10% by weight of the average value, preferably within about 5% by weight of the average value, and more preferably within about 1% by weight of the average value.

[0098] The thermoplastic polymer is of a type and grade sufficient to exfoliate graphene from graphite under shear strain. As previously mentioned, examples of the thermoplastic host polymer include the aforementioned polyethersulfone, polyarylate, polyphenylene ether / oxide, polyaryletherketone, polyvinyl chloride (PVC), polyetheretherketone (PEEK), polyetherketone (PEK), polyphenylene sulfide (PPS), polyethylene sulfide (PES), polyetherimide (PEI), polyethylene terephthalate (PET), polyethylene naphthalene dicarboxylate (PEN), polyamideimide (PAI), polyvinylidene fluoride (PVDF), polysulfone (PSU), polycarbonate (PC), aromatic thermoplastic polyester, aromatic polysulfone, thermoplastic polyimide, thermoplastic elastomer, polyethylene, high density polyethylene (HDPE), polypropylene (PP), polypropylene glycol (PG), polypropylene glycol ... Examples of suitable polymeric materials include, but are not limited to, polyethylene, high density polyethylene, low density polyethylene, polypropylene (PP), polystyrene (PS), acrylics such as polymethyl methacrylate (PMMA), ultra-high molecular weight polyethylene (UHMWPE), such as polyacrylonitrile (PAN), acrylonitrile butadiene styrene (ABS) copolymers, polytetrafluoroethylene (PTFE / TEFLON®), polyamide (PA), polylactic acid (PLA), polyglycolic acid (PGA), polylactic-glycolic acid copolymer (PLGA), polyphenylene oxide (PPO), polyoxymethylene plastics (POM / acetal), polydimethylsiloxane (PDMS), nylon, natural rubber (NR), acrylics, liquid crystal polymers (LCP), and mixtures of two or more thereof.

[0099] In some embodiments, the thermoplastic polymer is selected from the group consisting of polyamide, polystyrene, polyphenylene sulfide, high density polyethylene, acrylonitrile butadiene styrene (ABS) polymer, polyacrylonitrile, polylactic acid (PLA), polyglycolic acid (PGA), and polylactic-glycolic acid copolymer (PLGA). Polyamides include aliphatic polyamides, semi-aromatic polyamides, and aromatic polyamides. Aliphatic polyamides do not contain aromatic moieties. In some embodiments, the aliphatic polyamide is selected from the group consisting of polyamide-6,6 (nylon-6,6), polyamide-6 (nylon-6), polyamide-6,9; polyamide-6,10; polyamide-6,12; polyamide-4,6; polyamide-11 (nylon-11), polyamide-12 (nylon-12), and other nylons. Nylons are a well-known class of aliphatic polyamides derived from aliphatic diamines and aliphatic diacids.

[0100] Alternatively, other polyamides, also classified as nylons, are derived from the ring-opening polymerization of lactams, such as nylon-6 (PA-6, polycaprolactam), which is derived from caprolactam. In a particularly preferred embodiment, the aliphatic polyamide is polyamide-6,6, derived from hexamethylenediamine and adipic acid. Semi-aromatic polyamides contain a mixture of aliphatic and aromatic moieties and can be derived, for example, from aliphatic diamines and aromatic diacids. The semi-aromatic polyamide can be a polyphthalamide, such as PA-6T, derived from hexamethylenediamine and terephthalic acid. Aromatic polyamides, also known as aramids, contain aromatic moieties and can be derived, for example, from aromatic diamines and aromatic diacids. The aromatic polyamide can be a para-aramid, such as that derived from paraphenylenediamine and terephthalic acid. Representative of the latter is KEVLAR®.

[0101] In certain embodiments, the thermoplastic host polymer is an aromatic polymer. As defined herein, the term "aromatic polymer" refers to a polymer that includes aromatic moieties, which may be part of the polymer backbone or may be a substituent attached to the polymer backbone via a linker. Linkers include linear or branched alkylene groups such as methylene, ethylene, and propylene, heteroatoms selected from the group consisting of oxygen, nitrogen, and sulfur, and R selected from hydrogen and lower alkyl, -OCH2-, -CHO-, -OCH2 ... Linear or non-linear alkyl groups such as CH2CH2-, -CH2CH2O-, -OCH2CH2CH2-, -CH2OCH2-, -OCH(CH3)-, -SCH2-, -CH2S-, -NRCH2-, -CH2NR-, etc. or branched heteroalkylene groups. The linker may also be a heteroatom, such as -O-, -NR-, -S-, etc. If the linker contains sulfur, the sulfur atom may be oxidized. The aromatic moiety may be selected from monocyclic moieties, such as phenyl, and polycyclic moieties, such as indole naphthalene, anthracene, etc., which may be substituted with amino, NHR, NR2, halogen, nitro, cyano, alkylthio, alkoxy, alkyl, haloalkyl, CO2R, and combinations of two or more thereof, where R is as defined above. The aromatic moiety may also be a heteroaryl containing 1 to 3 heteroatoms, which may be substituted as described above, selected from the group consisting of oxygen, nitrogen, and sulfur. The aromatic polymer preferably contains a phenyl group, which may be substituted as described above, as part of the polymer backbone or as a substituent on the backbone, the latter optionally via a linker as described above. In certain embodiments, the optionally substituted phenyl group is included within the polymer backbone as an optionally substituted phenylene group. In certain other embodiments, the optionally substituted phenyl group is a substituent on a polymer backbone, optionally attached via a linker, as described above.

[0102] In one embodiment of the graphene reinforced polymer matrix composite disclosed above, the graphite may be doped with other elements to modify the surface chemistry of the exfoliated graphene nanoparticles. Preferably, the graphite is expanded graphite. Specifically and preferably, the surface chemistry or nanostructure of the dispersed graphite may be modified to bond with the polymer matrix to improve the strength and stiffness of the graphene reinforced composite. In one embodiment, directional alignment of graphene nanoparticles is used to obtain one-, two-, or three-dimensional reinforcement of the polymer matrix phase. In one embodiment, the polymer chains are intermolecularly cross-linked by single or multi-layer graphene sheets with carbon atoms having reactive bonding sites at the edges of the sheets.

[0103] In one embodiment of the present disclosure, the graphene reinforced polymer matrix composite further comprises at least one additive selected from fillers, dyes, pigments, release agents, processing aids, carbon fibers, compounds that improve electrical conductivity, and compounds that improve thermal conductivity.

[0104] In one embodiment, the graphite particles are prepared by crushing and grinding a graphite-containing mineral to millimeter-sized dimensions, reducing the millimeter-sized particles to micron-sized dimensions, and extracting micron-sized graphite particles from the graphite-containing mineral. In one embodiment, the graphite particles are distributed into a molten polymer phase using a single screw extruder having axially grooved elongational mixing elements or helically grooved elongational mixing elements. In one embodiment, the graphite-containing molten polymer phase is repeatedly extruded to induce exfoliation of the graphitic material and form an essentially uniform dispersion of single- and multi-layer graphene nanoparticles in a thermoplastic polymer matrix.

[0105] In some embodiments, crosslinked G-PMCs are formed by a method that includes distributing graphite microparticles into a molten thermoplastic polymer phase that includes one or more molten thermoplastic polymers. A series of shear strain events are then applied to the molten polymer phase, which successively exfoliates graphene with each event until the thickness of the graphene layers reaches a lower level, after which cleavage of the exfoliated multi-layer graphene sheets occurs, producing reactive edges on the multi-layer sheets that react with and crosslink the thermoplastic polymer.

[0106] Thus, activated graphene is formed when graphene cleaves across the basal plane, providing potential sites for linking or attaching other chemically labile groups for functionalization to the matrix. The crosslinking is therefore carried out preferably under an inert atmosphere or vacuum, with the exclusion of oxygen, so that the reactive edges are not oxidized or otherwise non-reactive. Forming covalent bonds between graphene and the matrix significantly improves the strength of the composite. Crosslinking polymers include those that are degraded by ultraviolet (UV) light. These include polymers that contain aromatics, such as polystyrene, e.g., benzene rings, polymers that contain tertiary carbons, such as polypropylene, and polymers that contain backbone oxygen, such as poly(alkylene oxide).

[0107] In some embodiments, the crosslinked G-PMC can be ground into particles and blended with a non-crosslinked host polymer to act as a toughening agent for the host polymer. The non-crosslinked polymer acquires the properties of a crosslinked polymer due to the chain entanglement between the two polymer species. The present disclosure also includes crosslinked polymers in particle form that can be blended with other polymers to form high strength composites. In one embodiment, crosslinked polystyrene and polymethyl methacrylate (PMMA) particles can be used as toughening agents for the host polymer. The composition according to the present invention includes a host thermoplastic polymer toughened with between about 1% and about 75% by weight of the crosslinked polymer particles of the present invention. In one embodiment, the host polymer is toughened with about 10% to about 50% by weight of the crosslinked polymer particles.

[0108] In some embodiments, the graphene-reinforced polymer matrix composite comprises graphite crosslinked with a polyamide. Preferably, the polyamide is an aliphatic or semi-aromatic polyamide. More preferably, the polyamide is an aliphatic polyamide selected from the group consisting of polyamide-6,6; polyamide-6 (nylon-6); polyamide-6,9; polyamide-6,10; polyamide-6,12; polyamide-4,6; polyamide-11 (nylon-11), polyamide-12 (nylon-12) and other nylons; especially PA-6,6 (nylon-6,6). Preferably, the graphene-reinforced polymer matrix composite comprises about 35% graphite prior to exfoliation in the graphene system. Polyamides crosslinked in this manner have very high specific strength properties and are suitable for automotive, aviation, marine, and aerospace applications. For example, the crosslinked polyamides may be used in engine parts such as pistons, valves, camshafts, turbochargers, etc. due to their high melting point and creep resistance. Forming the rotating portions of the turbine and compressor sections of a turbocharger, including their respective blades, from the crosslinked polyamides of this invention will reduce turbocharger lag due to the resulting weight reduction.

[0109] 4.Definition As used herein, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise. All technical and scientific terms are used herein unless otherwise defined.

[0110] As used herein, the term "and / or" means any one of the items, any combination of the items, or all of the items with which this term is associated.

[0111] The compositions of the present invention may comprise, consist essentially of, or consist of the claimed components. "Comprising" (and any of the configuration forms such as "comprise" or "comprise (third person singular)"), "having" (and any of the inclusion forms such as "having" or "having (third person singular)"), "listed" (and any of the inclusion forms such as "included" or "included (third person singular)"), or "containing" (and any of the inclusion forms such as "containing" or "containing (third person singular)") are not inclusive or open-ended and do not exclude additional, unrecited elements or method steps.

[0112] As used herein, the term "graphene" refers to the name given to a single layer of carbon atoms closely packed in a benzene ring structure. Graphene, when used alone, can refer to multilayer graphene, graphene flakes, graphene platelets, and pure, uncontaminated forms of few-layer graphene or single-layer graphene.

[0113] As used herein, graphite, the starting material from which graphene is formed, is composed of a layered planar structure in which the carbon atoms in each layer are arranged in a hexagonal lattice. The planar layers are defined as having an "a" axis and a "b" axis, with the "c" axis perpendicular to the plane defined by the "a" and "b" axes. The graphene particles produced by the method of the present invention have an aspect ratio defined by the "a" or "b" axis distance divided by the "c" axis distance. The aspect ratio values ​​of the nanoparticles of the present invention are greater than 25:1, and typically range from 50:1 to 1000:1.

[0114] As used herein, graphite microparticles are defined as graphite in which at least 50% of the graphite consists of multi-layer graphite crystals ranging from 1.0 to 1000 microns thick along the c-axis of the lattice structure. Typically, 75% of the graphite consists of crystals with a thickness of 100 to 750 microns. Expanded graphite may also be used. Expanded graphite is produced by forcing apart the crystal lattice planes of natural flake graphite and expanding the graphite, for example, by immersing the flake graphite in an acid bath of chromic acid and then in concentrated sulfuric acid. Expanded graphite suitable for use in the present invention includes expanded graphite with open edges at the bilayer level, such as MESOGRAF.

[0115] As used herein, the terms "nanographite sponge," "NGS," "graphene sponge," and "three-dimensional graphene network" are used interchangeably.

[0116] The publications disclosed herein are provided solely for their disclosure prior to the filing date of the present invention. Nothing herein should be construed as an admission that the present invention is not entitled to antedate such publications by virtue of prior invention. Further, the publication dates provided may be different from the actual publication dates which may need to be independently confirmed.

[0117] 5. Working Example The effect of post-fabrication heat treatment on the structure and properties of 35 wt% GNF-poly(ether-ether-ketone) (PEEK) composites was investigated. Composite samples were fabricated by a specially designed exfoliation / injection molding machine capable of in situ exfoliation and reduction of 300 μm graphite sheets in molten polymer to few-layer or single-layer graphene. PEEK samples were prepared by the method described in U.S. Pat. No. 10,329,391, the disclosure of which is incorporated by reference. Subsequent heat treatments were characterized by at least one extended annealing at a temperature just above the melting point of the polymer matrix phase, where a reaction occurs between the GNFs and the polymer matrix.

[0118] 35wt% GNF-PEEK composite material Heat treatment of the 35 wt% GNF-PEEK samples was carried out in a resistively heated furnace, with each sample positioned vertically in the furnace. In the first experiment, the composite specimens were heated at a rate of 5°C / min to 200°C, 400°C, and 600°C, and held at each temperature for 20 min. Samples heated at 400°C and 600°C for 20 min showed significant decomposition of the PEEK matrix phase, leaving a porous graphitic material. Additionally, the specimens showed swelling due to the accumulation of PEEK decomposition gases within the samples. As expected from buoyancy effects, most of the expansion occurred in the top half of the specimens.

[0119] One-step heat treatment of the 35 wt% GNF-PEEK samples above 380°C (well above Tm) caused a global swelling due to gasification of the PEEK matrix. As expected, decomposition of the PEEK matrix starts at the sample surface and propagates to the interior of the sample, thus creating a porous preform of graphene nanoflakes. A two-step heat treatment was also used to modify the structure and properties of the 35 wt% graphite-PEEK composites. It involved heating the composites at 200°C for 20 hours and then above 380°C for 18 hours, after which some samples were heat treated at 600°C for 60 minutes.

[0120] After a post-heat treatment at 600 °C for 60 min, the decomposition of the PEEK matrix was essentially complete, leaving a porous graphite preform that exhibited some stiffness. The latter is due to the presence of some of the pyrolytic PEEK (amorphous carbon) forming bridges between adjacent GNFs. Interestingly, this effect opens up the opportunities for subsequent infiltration of the porous graphite preform with reactive or non-reactive materials. The same results were obtained in a single step of heating the sample at 600 °C for 1 h.

[0121] Small samples of 35 wt% GNF-PEEK before and after post-heat treatment at 600 °C were immersed in concentrated sulfuric acid (98%) for 24 h. The heat-treated samples survived the acid immersion, whereas the untreated samples did not. In fact, the latter completely decomposed and formed a fine suspension of GNFs in the acid solution. This test shows that the annealing treatment introduces effective bonds between adjacent GNFs in the composite, and that a reasonably stiff porous GNF-based structure is achieved once the remaining PEEK is removed by acid etching. One possible mechanism is the formation of pyrolytic carbon bridges between adjacent GNFs in the porous structure.

[0122] All of the methods and apparatus disclosed and claimed herein can be made and executed without undue experimentation in light of the present disclosure. Although the present invention has been described with respect to preferred embodiments, it will be apparent to those skilled in the art that variations may be applied to the apparatus, the method, and the sequence of steps of the method without departing from the concept, spirit, and scope of the invention. More specifically, it will be apparent that certain components may be added to, combined with, or substituted for the components described herein while the same or similar results would be achieved. All such similar substitutes and modifications apparent to those skilled in the art are deemed to be within the spirit, scope, and concept of the invention as defined.

[0123] The above-disclosed features and functions, and alternatives, may be combined into many other different systems or applications. Various presently unforeseen or unanticipated alternatives, modifications, variations, or improvements may occur to those skilled in the art, each of which is also intended to be encompassed by the disclosed embodiments.

Claims

1. A method for forming a nano-graphite sponge comprising: (a) dispersing graphite microparticles in a molten polymer phase formed from a polymer; (b) after step (a), applying a series of shear strain events to the molten polymer phase such that the molten polymer phase successively exfoliates the graphite with each event until at least 50 weight percent of the graphite microparticles are exfoliated and a distribution of graphene nanoparticles having a thickness along the c-axis direction of less than 50 nanometers is formed in the molten polymer phase, thereby forming a graphene-reinforced polymer matrix composite; (c) after step (b), heating at or near the melting temperature of the polymer phase sufficiently to melt the polymer without decomposing or gasifying the polymer phase; (d) after step (c), heating the graphene reinforced polymer matrix composite at or near a gasification temperature of the polymer for a duration sufficient to cause the polymer to decompose and gasify to form a nano-graphite sponge; and (e) after step (d), heating the nano-graphite sponge at a temperature above the melting and gasification temperature of the polymer phase until residual polymer decomposes and the graphite / graphene particles comprise 70-100 wt.% of the total weight of the nano-graphite sponge.

2. 13. The method of claim 1, further comprising: (f) after step (e), vapor or liquid infiltrating the nano-graphite sponge with a precursor comprising an electroactive element selected from the group consisting of lithium, silicon, sodium, sulfur, and combinations thereof to form an electroactive element intercalated nano-graphite sponge.

3. 3. The method of claim 1, wherein the step of dispersing the graphite microparticles comprises dispersing the graphite microparticles in the molten polymer phase, and wherein at least 50% by weight of the graphite microparticles are comprised of p-graphite crystallites having a thickness along a c-axis direction between 1.0 and 1000 micrometers.

4. 4. The method of claim 1, wherein the step of applying a series of shear strain events comprises applying a series of shear strain events to the molten polymer phase such that a shear stress in the molten polymer phase is equal to or greater than an interlaminar shear strength (ISS) of the graphite micro-particles.

5. 5. The method of claim 1, wherein the series of shear strain events is applied until at least 90% by weight of the graphite microparticles are exfoliated to form a dispersion of the graphene nanoparticles in the molten polymer phase less than 50 nanometers thick along the c-axis direction; or the series of shear strain events is applied until cleavages in the graphene nanoparticles are formed across the basal planes of the graphene nanoparticles, the edges of the cleavages containing one or more reactive free radical bonding sites that react with the molten polymer to provide a composite material in which thermoplastic polymer chains are covalently bonded directly to the graphene nanoparticles and intermolecularly crosslinked.

6. 6. The method of claim 1, wherein the graphene reinforced polymer matrix composite comprises chains of thermoplastic polymer intermolecularly crosslinked to the graphene nanoparticles via covalent bonds.

7. 7. The method of any one of claims 1 to 6, wherein the graphite is doped with other elements that modify the surface chemistry of the exfoliated graphene nanoparticles, thereby improving the bond strength between the exfoliated graphene and the polymer.

8. 8. The method of claim 1, wherein the graphene reinforced polymer matrix composite comprises 0.1% to 50% by weight of graphene.

9. 9. The method of any one of claims 1 to 8, further comprising forming a uniform distribution of one or more additives in the molten polymer phase, said additives promoting intercalation of an electroactive element selected from the group consisting of lithium, silicon, sodium, sulfur and combinations thereof into the nano-graphite sponge.

10. The method of any one of claims 1 to 9, wherein the graphite microparticles are incorporated into the polymer matrix using a single screw extruder equipped with axially grooved elongational mixing elements or helically grooved elongational mixing elements.

11. 11. The method of any one of claims 1 to 10, wherein the polymer matrix composite is repeatedly extruded to induce exfoliation of the graphite to form a uniform dispersion of graphene nanoparticles in the polymer matrix composite.

12. The polymer may be selected from the group consisting of polydimethylsiloxane (PDMS), sodium polyacrylate, polymethylmethacrylate (PMMA), acrylonitrile, acrylonitrile butadiene styrene (ABS) copolymer, polyacrylonitrile (PAN), aromatic thermoplastic polyester, liquid crystal polymer, polyaryletherketone, polycarbonate (PC), polyetheretherketone (PEEK), polyetherimide (PEI), polyetherketone (PEK), sulfurized polyethylene (PES), polyethylene terephthalate (PET or PETE), low density polyethylene (LDPE), high density polyethylene (HDPE), polyglycolic acid (PGA), polylactic acid (PLA), polylactic-glycolic acid copolymer (PLGA), polyoxymethylene plastic (POM / acetal), poly 12. The method of any one of claims 1 to 11, wherein the thermoplastic elastomer is selected from the group consisting of polyphenylene ether, polyphenylene oxide (PPO), polyphenylene sulfide (PPS), polypropylene (PP), polystyrene (PS), polysulfone (PSU), polytetrafluoroethylene (PTFE), polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), thermoplastic elastomers, thermoplastic polyimides, ultra-high molecular weight polyethylene (UHMWPE), semi-aromatic polyamides, aromatic polyamides, polyamide-11 (nylon-11), polyamide-12 (nylon-12), polyamide-4,6, polyamide-6 (nylon-6), polyamide-6,10, polyamide-6,12, polyamide-6,6 (nylon-6,6), polyamide-6,9, and mixtures of two or more thereof.

Citation Information

Patent Citations

  • Graphene Reinforced Polymer Matrix Composite

    JP2017531052A

  • Low friction wear resistant graphene films

    US20150367381A1

  • Targeted content presentation system using contractual data

    US20160042390A1

  • Graphene-metal chalcogenide porous material

    US20160332136A1

  • Method for manufacturing expanded graphite and method for manufacturing flake graphite

    WO2014054441A1